Domestication and varietal diversification of Old World cultivated cottons (Gossypium sp.) in the Antiquity - Christopher Viot (Revue d'ethnoécologie)
Textile use of the cotton fibres from the Old World species Gossypium arboreum (Tree Cotton) and G. herbaceum (Levant Cotton) started around eight thousand years ago and possibly earlier. During the third millennium before the present, cotton cultivation, textile use and trading developed strongly in many places of the Indian Subcontinent and the Near East, but the species involved are often undetermined. Gossypium arboreum and G. herbaceum are difficult to distinguish morphologically when dealing with archaeological remains. Many traditional varieties have been described for each of these two species; an evolution is apparent from perennial, rather primitive forms through to annual varieties and modern phenotypes, with adaptations to cultivation in diverse conditions, including cold climates and short summers. The present work examines which varieties could have been cultivated in the Antiquity and in which regions had cotton cultivation spread then. Some extant varieties are hypothesized as close to the cultivars of Antiquity. The geographic distribution of each species probably reflects the initial domestication region and the subsequent adaptations, particularly regarding climate. Recent progress on ancient DNA analysis should permit easier specific assignments of archaeological remains of cotton seeds, fibres, threads or fabrics.